A Systematic Scoping Review of Team-Level Job Redesign in Organizations - Edelmann, Charlotte M.; Bakker, Arnold B.; Derks, Daantje (Sage publications, 2026)
As organizations seek to enhance team collaboration and productivity, team-level job redesign has become a critical focus in organizational psychology and management. However, research mainly emphasizes individual-level redesign, leaving gaps in understanding how teams collectively shape their work. This systematic scoping review synthesizes evidence on team-level job redesign in organizations, with two objectives: (1) identifying study characteristics; and (2) analyzing concepts and practices teams use to shape jobs and improve well-being and performance collaboratively. Using a mixed studies review approach, which incorporates evidence from both qualitative and quantitative research designs, we searched electronic databases (e.g., Web of Science, PsycINFO, Scopus) and gray literature for empirical studies published in English from January 2000 to September 2025. After screening 12,946 studies, 90 met the inclusion criteria for the final analysis. These studies varied in methods, interventions, and outcomes. The review not only synthesizes key findings and identifies important knowledge gaps but also offers recommendations to advance research and practice in team-level job redesign. Beyond mapping existing studies, it introduces a typology of team-level job redesign initiatives – ‘cross-functional’, ‘bottom-up’, and ‘hybrid’ – providing a structured framework to integrate diverse approaches and guide future research.
Keywords: employee well-being; job crafting; job design; systematic scoping review; teamwork; fi=Henkilöstöjohtaminen|en=Human Resource Management|